Ovarian cancer: progression of tumors - Mor, Gil (Henry Stewart Talks, 2019)
The origin of ovarian cancer, Epithelial ovarian cancer cells, The formation of ovarian tumors, Luteal cells and ovarian cancer, The metastatic process in ovarian cancer, Response to chemotherapy, The recurrence of cancer stem cells